Development and validation of the Gastrointestinal Endoscopy Satisfaction Questionnaire (GESQ) - Hutchings, Hayley A.; Cheung, Wai-Yee; Alrubaiy, Laith; Durai, Dharmaraj; Russell, Ian T.; Williams, John G. (Endoscopy, 2015)
Background and study aims: Patient satisfaction is a key indicator of the quality of gastrointestinal (GI) endoscopy. The aim of this study was to develop and validate a specific patient satisfaction questionnaire for patients undergoing GI endoscopy – the Gastrointestinal Endoscopy Satisfaction Questionnaire (GESQ).Patients and methods: We developed and validated the GESQ within the context of a national multi-institution nurse endoscopy trial, based in secondary care, in three stages: (1) item generation with a panel of patients and professionals following a detailed literature review to identify the most relevant items from existing scales; (2) development and piloting of a draft questionnaire on a sample of patients referred for GI endoscopy; and (3) testing of the questionnaire within a large multicenter pragmatic randomized trial. We undertook psychometric analysis of the questionnaire to identify the underlying dimensions and assessed the questionnaire for reliability and validity.Results: The final version of the GESQ contains 21 items. Principal components analysis revealed four subscales with high internal consistency: skills and hospital (seven items; Cronbach’s alpha 0.83), pain and discomfort during and after endoscopy (four items; Cronbach’s alpha 0.84), information before endoscopy (five items; Cronbach’s alpha 0.80), and information after endoscopy (five items; Cronbach’s alpha 0.76).Conclusions: The four identified subscales are clinically relevant and correspond to domains of patient satisfaction identified in previous studies. Our development and validation of the GESQ confirmed that it is a valid, reliable, interpretable, and acceptable tool to measure satisfaction in patients who have undergone a GI endoscopy.